THE INFLUENCE OF TRAINING AND COMPETENCE ON THE PERFORMANCE OF HARPER HOTEL JAKARTA EMPLOYEES - Asriadi, Fajar (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of training and competence on employee performance at Harper Hotel Jakarta. The research method used in this research is descriptive with a quantitative approach. The population amounted to 58 people, so the sampling technique was used with the saturated sample method and the number of samples obtained in this study were 58 respondents. Data analysis techniques using multiple linear regression. The results showed that: (1) There is a positive and significant effect of training variables on employee performance at Harper Hotel Jakarta. This is evidenced by the value of tcount > ttable, namely 4.352 > 2.004 with a probability value (significance) = 0.000, which is below 0.005. (2) There is a positive and significant effect of competency variables on employee performance at Harper Hotel Jakarta. This is evidenced by the value of tcount > ttable, namely 7.381> 2.004 with a probability value (significance) = 0.000, which is below 0.005. (3) There is a positive and significant effect of training and competency variables on employee performance at Harper Hotel Jakarta. This is evidenced by the value of Fcount > Ftable, namely 26.75 9> 3.16 with a probability value (significance) = 0.000, which is below 0.005.